Pengembangan Media Simulation Board Pada Mata Pelajaran Bahasa Indonesia - Maritasari, Donna Boedi (Universitas Hamzanwadi, 2017)
This study aims to produce teaching materials in the form of a media simulation board in learning Indonesian. This research is also useful to find out the results of the development of learning in improving students' reading skills. The development model used in this study is the Borg & Gall model. The test subjects in this study were fifth grade students of SDN 01 Dasan Lekong. It can be concluded that the product developed in the form of learning media can be said to be suitable for use in the learning process. From the data from the field trial results obtained data completeness percentage on student learning outcomes tests which reached 73, 25%% with good criteria. Data from the results of the experts also showed good conversions ranging from media experts 3, 00, material experts 3.38 and the last class 3.95 teachers.